Relationship between Openness to Experience and Perception to Political Organizations to Workplace Deviant Behavior - Dwi Hastuti; Idris Mohd Noor; Abdullah Osman (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
This study aims to determine the relationship that exists between openness to experience (one of the personality traits) and perceptions of organizational politics to workplace deviant behavior. Research was conducted by collecting 263 responses from the civil servants in Pekanbaru, Riau. Applying the latest PLS 3.0 analysis tools the results of this research identified positive correlation between openness to experience and perception of the political organization to workplace deviant behavior. The perception of the organization politics has managed to moderate the relationship between openness to experience deviant behavior in the workplace.